In Vitro Antiplasmodial Activity of Flower Extracts from combretum leprosum mart (mofumbo) - Passarini, Guilherme Matos; Medeiros, Daniel Sol; Meneguetti, Dionatas Ulisses de Oliveira; Lima, Renato Abreu; Facundo, Valdir Alves; Medeiros, Patrícia Soares de Maria de (Ciência e Natura, 2016)
Malaria is the cause of hundreds of deaths per year , besides putting billions of people at risk of developing disease. When it comes to its therapy, the drugs used currently are losing its efficacy due to increase inn the frequency of resistant strains of the parasite, highlight the importance for the serach of new classes of molecules prsentign antiplasmodial activity. In the present work, the antiplasmodial activities of five extracts from the flowers of Comretum leprosum are described. The method employed for obtaingine the extracts was silica gel column chromatography, and the techniques used for the analysis of antiplasmodial activity and citotoxicity were ELISA and MTT respectively, were a selectivitu index was calculated after the obtainign of these two values. The extract presenting the highest antiplasmodial activity was the chloroform extract, however, this extrac also presented the higther cytotoxicity and therefore the extract presenting the best overall activity was the hexane extract. The study deminstrated the plant Combretum leprosum has active substances against P. falciparum and therefore is a potential to be expored in funther pharmacological studies.